2019
DOI: 10.1186/s12966-019-0833-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying food marketing to teenagers: a scoping review

Abstract: Background Teenagers are aggressively targeted by food marketing messages (primarily for unhealthy foods) and susceptible to this messaging due to developmental vulnerabilities and peer-group influence. Yet limited research exists on the exposure and power of food marketing specifically to teenage populations. Research studies often collapse “teenagers” under the umbrella of children or do not recognize the uniqueness of teen-targeted appeals. Child- and teen-targeted marketing strategies are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 122 publications
(22 reference statements)
2
60
0
1
Order By: Relevance
“…Our results found the rates of food advertising during adolescent-targeted programming to be alarmingly similar to rates during adult-targeted programming. This is concerning as adolescents are not immune to the effects of food marketing [53]. In fact, not only are adolescents less likely to be critical of food advertising than adults, but this age group is also highly targeted due to their purchasing power [17,53].…”
Section: Food Advertising To Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results found the rates of food advertising during adolescent-targeted programming to be alarmingly similar to rates during adult-targeted programming. This is concerning as adolescents are not immune to the effects of food marketing [53]. In fact, not only are adolescents less likely to be critical of food advertising than adults, but this age group is also highly targeted due to their purchasing power [17,53].…”
Section: Food Advertising To Adolescentsmentioning
confidence: 99%
“…This is concerning as adolescents are not immune to the effects of food marketing [53]. In fact, not only are adolescents less likely to be critical of food advertising than adults, but this age group is also highly targeted due to their purchasing power [17,53]. Food companies strategically advertise to adolescents, as evidenced by the elevated rate of food advertising during adolescent-programming in July 2018 (i.e., summer vacation); the time during which they are more likely to be watching television.…”
Section: Food Advertising To Adolescentsmentioning
confidence: 99%
“…In the United States (US), 25.4% of children and 21.0% of adolescents had obesity in 2017, and 26.3% and 24.2% of children and adolescents may be affected by obesity by 2030 2 . Robust evidence suggests that food and beverage marketing practices (e.g., print and broadcast media, celebrity endorsement, or interactive social media) negatively influence the dietary behaviors of children (0–11 years), adolescents (12–18 years), and young adults (19–35 years), which increases their risk of obesity and diet‐related noncommunicable diseases (NCD) 3–7 …”
Section: Introductionmentioning
confidence: 99%
“…Content analysis research, which focuses on the marketing output as the unit of analysis, highlights at least three ways in which the marketing of HFSS foods may elicit positive emotional responses or shape product and/or brand perceptions among children and adolescents. First, studies have shown that marketing for HFSS foods often uses attractive, fun, and engaging design features, such as visually stimulating graphics, branded characters, auditory cues, and immersive advergames [4,[21][22][23][24]. Second, marketing also reportedly features content which may resonate with, or create a positive emotional response among, children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Second, marketing also reportedly features content which may resonate with, or create a positive emotional response among, children and adolescents. This includes references to celebrities and popular culture, featuring brand equity characters (e.g., cartoon brand mascots), linking the brand to attractive and desirable identities or lifestyles, or featuring humorous content [21][22][23][24]. Third, marketing may place a greater emphasis on the sensory or emotive benefits of a product (e.g., taste or texture), as opposed to presenting objective information about nutrition and health, or may use ambiguous language that implies greater nutritional benefit than is actually present (e.g., fruit-flavored) [25][26][27].…”
Section: Introductionmentioning
confidence: 99%